2012
DOI: 10.1007/s12144-012-9159-9
|View full text |Cite|
|
Sign up to set email alerts
|

Are You Really Happy? Children’s Understanding of Real vs. Pretend Emotions

Abstract: This paper studies children’s capacity to understand that the emotions displayed in pretend play contexts do not necessarily correspond to internal emotions, and that pretend emotions may create false beliefs in an observer. A new approach is taken by asking children about pretend emotions in terms of pretence-reality instead of appearance-reality. A total of 37 four-year-olds and 33 six-year-olds were asked to participate in tasks where they had to pretend an emotion or where they were told stories in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
17
0
3
Order By: Relevance
“…Previous literature has shown that young children are capable of realizing other children may pretend to be sad for playful reasons (see Sidera et al, 2013). The current study found that this knowledge develops gradually between the ages of 4 and 6, and is well-established from the age of 6 years, as all children in the older group recognized the expression of pretend sadness.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous literature has shown that young children are capable of realizing other children may pretend to be sad for playful reasons (see Sidera et al, 2013). The current study found that this knowledge develops gradually between the ages of 4 and 6, and is well-established from the age of 6 years, as all children in the older group recognized the expression of pretend sadness.…”
Section: Discussionsupporting
confidence: 68%
“…Children's ability to understand that the real emotion of a person may differ from their emotional expression has often been studied in contexts of deception (see Sidera et al, 2013). Children begin to control their emotional expressions at the age of 4; however, at that age they are not yet able to deceive other people through emotional expression.…”
Section: Children's Recognition Of Emotional Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that the explicit understanding of pretend emotions (e.g., understanding that a child is crying because it is a part of a game and not because he or she is actually sad) is difficult before the age of 4 years, and develops between the ages of 4-6 years (Mizokawa, 2011;Peterson & Wellman, 2009). However, grasping the implications of pretend emotions for the beliefs of observers (people can be deceived about the real emotions of a pretender) continues to be difficult after the age of 6 (Sidera, Amadó, & Serrat, 2013).…”
Section: Pretend Emotion Understandingmentioning
confidence: 99%
“…This developmental progression led us to conduct a comparison of three age groups in the present study. However previous studies evaluating hearing children's understanding of pretend emotions used narratives with pictures with a high linguistic load (Mizokawa, 2011;Sidera et al, 2013). This method is not appropriate for children who are DHH, as evaluations of ToM and emotion understanding require a technique with lower linguistic demands such as silent videos.…”
Section: Pretend Emotion Understandingmentioning
confidence: 99%